2005
DOI: 10.1007/s00438-004-1091-8
|View full text |Cite
|
Sign up to set email alerts
|

p53 polymorphisms in Russia and Belarus: correlation of the 2-1-1 haplotype frequency with longitude

Abstract: Four different polymorphisms in the human p53 gene (a 16-bp duplication in intron 3, and three RFLPs: for Bsh1236I at codon 72, for MspI in intron 6 and for BamHI in the 3' flanking region) and extended haplotypes were studied in nine geographically diverse populations from Russia and Belarus. The Yakuts differed from all other populations, as they had a significantly higher frequency of the BamHI A1 allele. Most populations did not differ significantly from each other in the frequency of the Bsh1236I polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
(36 reference statements)
2
14
1
1
Order By: Relevance
“…In another study, several haplotypes, or combinations of susceptibility alleles, were associated with lung cancer in Caucasians (37). Despite differences in the alleles examined in these studies and our report, given the observed linkage between the three polymorphisms (35,37,39,44,45) and the position of the haplotype on TP53 associated with lung cancer in our study, our results and previous studies suggest that this region of TP53 may have a role in modulating lung cancer susceptibility. No previous studies examined the association of TP53 haplotypes with lung cancer survival.…”
Section: Discussioncontrasting
confidence: 47%
“…In another study, several haplotypes, or combinations of susceptibility alleles, were associated with lung cancer in Caucasians (37). Despite differences in the alleles examined in these studies and our report, given the observed linkage between the three polymorphisms (35,37,39,44,45) and the position of the haplotype on TP53 associated with lung cancer in our study, our results and previous studies suggest that this region of TP53 may have a role in modulating lung cancer susceptibility. No previous studies examined the association of TP53 haplotypes with lung cancer survival.…”
Section: Discussioncontrasting
confidence: 47%
“…62 The observation that the ratio of proline to arginine alleles in individuals changes as the latitude changes from the equator to the north pole already suggests that selection is playing a role upon these alleles. 63 There are several studies that suggest that one or the other allele could influence the occurrence or progression of cancer. 64,65 At present however the results are confusing and a better understanding of the role of these two alleles in the pathway will be important.…”
Section: Questions About the P53 Pathway In A Larger Contextmentioning
confidence: 99%
“…Here, we will present only two polymorphisms that have been shown to impact the function or level of expression of p53, an allele that carries a 16 base-pair (bp) duplication in intron 3 localized at nucleotide 11 951 (denoted þ 16), and an allele that carries a G to C transversion in intron 6 at nucleotide 13 964 (denoted G-C). The allele frequencies of these two non-coding polymorphisms, which show significant differences between populations from Russia and Belarus, have recently been correlated to ethnical variations (Khrunin et al, 2005).…”
Section: Polymorphisms In P53 Non-coding Regionsmentioning
confidence: 99%